A study of the prevalence of group B streptococci in the third trimester of pregnancy - Tambe, Vikas; Shokeen, Versha; Bal, Himadri; Mishra, Ajita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Group B Streptococci (GBS) is an important cause of early onset neonatal sepsis and the maternal colonization of this organism is a key factor in the occurrence of GBS associated morbidity and mortality in the newborns. Timely recognition of its presence in the genital tract of a pregnant women and intrapartum antibiotic prophylaxis can significantly bring down the burden of the disease in neonates. A cross sectional study was conducted on antenatal women during 35-37weeks of gestation to evaluate the prevalence of Group B Streptococci in third trimester of pregnancy and explore the feasibility of including GBS screening in the routine antenatal investigation protocol. Methods: 200 antenatal women satisfying the exclusion/inclusion criteria were recruited for the study. Vaginal and perianal swabs were collected using sterile swab sticks and inoculated using the specified media. Beta hemolysis and typical colonies were looked for under microscope. Positive cases were subjected to intrapartum antibiotic prophylaxis and the neonates were observed for 72 hours to look for any signs of sepsis. Results: It was found that 2% of the women screened were positive for GBS .While none of the newborns of the 4 positive cases showed any signs of sepsis. Conclusions: Prophylactic intrapartum prophylaxis against GBS has shown to decrease the chances of neonatal sepsis but more detailed and robust studies are required before incorporating routine screening in our antenatal care system.